Correction: Urban vectors of Chagas disease in the American continent: A systematic review of epidemiological surveys. - Ana Laura Carbajal-; Paz Sánchez-Casaccia; Romina Valeria Piccinali; Yael Provecho; Liliana Salvá; Sergio Meli; Florencia Cano; Ricardo Hernández; Julieta Nattero (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0011003.].